2011
DOI: 10.1177/008124631104100106
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Work-Family Enrichment and Work-Family Satisfaction Outcomes

Abstract: In this study, we investigate the positive aspects of the interface between work and family by examining the relationship between work-family enrichment and work-family satisfaction outcomes. Employees ( N = 336) at a national retail chain completed a survey questionnaire. Hierarchical multiple regression analysis showed that work-to-family enrichment explains a significant proportion of the variance in both job satisfaction and career satisfaction and that the affective component of family-to-work enrichment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 35 publications
1
24
0
6
Order By: Relevance
“…Hassan et al (2009) reported that work-family enrichment increased employees' job satisfaction in a study of employees from three public and three private sector organizations in Sarawak, Malaysia. Similar results were reported by (McNall et al, 2010b;Jaga and Bagraim, 2011;Masuda et al, 2012). A longitudinal study of Taiwanese employees by Lu (2011) reported a significant positive relationship between work-family enrichment and job satisfaction.…”
Section: Relationship Between Work-family Enrichment and Job Satisfacsupporting
confidence: 83%
“…Hassan et al (2009) reported that work-family enrichment increased employees' job satisfaction in a study of employees from three public and three private sector organizations in Sarawak, Malaysia. Similar results were reported by (McNall et al, 2010b;Jaga and Bagraim, 2011;Masuda et al, 2012). A longitudinal study of Taiwanese employees by Lu (2011) reported a significant positive relationship between work-family enrichment and job satisfaction.…”
Section: Relationship Between Work-family Enrichment and Job Satisfacsupporting
confidence: 83%
“…We coded marital status as 1 for married and 0 for unmarried, and we coded education as 1 for middle school and below; 2 for high school; 3 for college; 4 for bachelor's degree; 5 for master's degree and 6 for Ph.D. degree. 1 We also controlled for age because existing research suggests that age has an influence on an individual work-family enrichment experience (Jaga & Bagraim, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…(2013) bir ölçeğin ölçüt bağımlı geçerliğinin sağlanması için değişkenler arasındaki ilişkilerin beklentiler doğrultusunda bulunması gerektiğini ifade etmişlerdir. Buna göre, daha önce yapılan çalışmalar doğrultusunda, iş-aile zenginleşmesinin aile tatmini (Jaga ve Bagrain, 2011), ve çalışan performansı (van Steenbergen ve Ellemers, 2009;Carlson vd., 2011) ile pozitif, buna karşılık işten ayrılma niyeti (McNall vd., 2010; Russo ve Buonocore, 2012; Mihelič, 2014) ile negatif ilişkili olması beklenmektedir.…”
Section: şEkil 1 İş-aile Zenginleşmesi Modeli (Powell Ve Greenhaus unclassified
“…Undertaking different roles in more than one field allows the resources acquired in one role provide personal development in the other role, getting better skills and being in a better mood, which is a situation that creates positive effects on the life of the individual. Studies conducted reveal that work-family enrichment increase job satisfaction (Carlson et al, 2010;Carlson et al, 2006;, family satisfaction (Jaga and Bagrain, 2011), commitment to work (Tims et. al., 2015;De Klerk et al, 2015) and performance (van Steenbergen and Ellemers, 2009;; whereas, it decreases intention to leave the company Russo and Buonocore, 2012;Mihelič, 2014) and stress.…”
Section: Introductionmentioning
confidence: 99%